Dialética política no ensino fundamental: Triste Fim de Policarpo Quaresma x Carta Magna - Paulino, Elciane de Lima (2018)
After the age of 90, the researches related to the teaching of language began supporting on a design of language for interaction, suggesting that the textual and discursive genres to be taken as objectives of teaching-learning. Notwithstanding, to use the genres as learning objectives has become ever a great challenge, so much that the students pass to the last school year of elementary school with difficulties to use procedures necessary to acess contents and to produce senses, especially, in the matter of the gender analisys and application of non-linear strategies during the processing of reading, while also underpinning knowledges and establishing relations between principles. That way, seeking to contribute to the education of readers and critical citizens, we developped this dissertation which consists of presentation of research-action conducted in a classroom of 9th year of the elementar school, in a state school in Guarabira-PB. The purpose of research was analysed the political nature of the romance Triste Fim de Policarpo Quaresma, by Lima Barreto, considering the dialogism forms through of language, articulating this speech with the Brazilian Federal Constitution and its precepts the citizens rights. We have taken as basis the researches by Bakhtin (2000 and 2014); Candido (2006); Cosson (2014); Brasil (1998); Fiorin (2016); Moisés (2006); among others. After the choose of the gender romance, we have elabored the research of bibliographic, analytical, descriptive and interventional value, which involved the participation of researchers and investigated people, to actuate to minimize the problems. For this purpose, we have systematized the activities, linking the central ideas: use of the oral and written language and reflexion about the language (BRASIL, 1998), through the sequence expanded of the literacy proposed by Rildo Cosson (2014). That way, the data collection arose from the pracitces of oral communication, reading and writing productions in the classroom, since diagnostic activity, which consisted in identifying the preferences of reading of the learners, until the stages of sequence expanded (motivation, introduction, reading, first interpretation, contextualization, second interpretation and expasion). Therefore, the body of the research consists of the made produtions in each step of the intervention. After the execution of the interventional proposal, the analysis carried directed towards greater participation and motivation of the students for the reading, analysis and language reflexion, as well as for the acquisition of the new procedures and a greater interaction with the literary text. The learners went other than building of the meanings of the literary text, after understanding in the reading the expressive and humanizing power of the literature, as well as the possibility of a solid social orientation for the citizenship exercise on the basis of thea acquired knowledges.